KONSEP PEMBERDAYAAN PENINGKATAN EKONOMI PEMBUDIDAYA RUMPUT LAUT (STUDI KASUS DI KABUPETEN SERAM BAGIAN BARAT) - Ivonne Raystika Gretha Kaya; Angel Ruban; Manuel Kaya; Fildo de Lima; Astaman Amir (Universitas Pattimura, 2022)
Generally, the income of seaweed farmers just able to be used for their daily needs, so this study aims to find a concept for increasing farmers income which is planned, systematic and sustainable. This condition must also rely on the ability of seaweed farmers to manage their business optimally. This study used a survey method. 57 seaweed farmers as respondent are selected with random technique. The concept of empowerment in increase the economy of seaweed farmers in accordance with the conditions in West Seram District are assistance of: capital, infrastructure development, mentoring, institutional strengthening and business partnerships.